Рroviding technical and forensic investigative actions in the investigation of acts of terrorism - Chukumov, G.B. (Bulletin of the Karaganda University “Law Series”, 2018)
This article discusses the features of technical and forensic identification and search in the investigation of crimes related to terrorism. The article reveals the topic of search and identification in the investigation of acts of terrorism, based on the previous experience of forensic scientists, legal norms, law enforcement statistics, scientific and practical materials containing modern data on technical and forensic techniques and equipment, which are still successfully used in the investigation of acts of terrorism here and abroad. The study of the prospects of technical and forensic identification and search in the Commission of a terrorist act, require the use of a variety of scientific methods based on the provisions of the materialistic dialectic of historical conditionality, objective laws of development and interaction of phenomena. The legislation of the Republic of Kazakhstan requires the presence of witnesses and representatives of the local Executive body during the investigation to avoid unnecessary risk to the life and health of those present. During the search, firearms, cold weapons, ammunition, explosive materials or parts for their manufacture, poisons, as well as wanted terrorists are searched, and if the presence of the above-mentioned persons cannot be ensured, there is a conflict between criminal procedure norms and security requirements.